2015
DOI: 10.1111/jpn.12413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of raw soya bean particle size on productive performance and digestion of dairy cows

Abstract: Differing soya bean particle sizes may affect productive performance and ruminal fermentation due to the level of fatty acid (FA) exposure of the cotyledon in soya bean grain and because the protein in small particles is more rapidly degraded than the protein in large particles, which influence ruminal fibre digestion and the amounts of ruminally undegradable nutrients. The objective of this experiment was to investigate the effects of raw soya bean particle size on productive performance, digestion and milk F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Dietary fat supplementation often increases the lipoprotein cholesterol exportation by the intestine, the major site of cholesterol synthesis in ruminants (Noble, 1981). In agreement with the current study, Naves et al (2016) fed WRS to lactating cows and reported a trend to decreased blood glucose concentration and an increase in blood cholesterol concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary fat supplementation often increases the lipoprotein cholesterol exportation by the intestine, the major site of cholesterol synthesis in ruminants (Noble, 1981). In agreement with the current study, Naves et al (2016) fed WRS to lactating cows and reported a trend to decreased blood glucose concentration and an increase in blood cholesterol concentration.…”
Section: Discussionsupporting
confidence: 92%
“…This increase was mainly due to smaller particle size and higher degradability of CP of ground FB compared with SBM and rolled FB. Reducing particle size of peas (Vander Pol et al, 2009) and raw soybean (Naves et al, 2016) via physical processing has also been reported to enhance CP digestibility. In contrast, Zagorakis et al (2015) reported higher CP digestibility in rams fed SBM compared with those fed ground FB.…”
Section: Intake and Apparent Total-tract Digestibilitymentioning
confidence: 99%
“…Although the DM intake of cows consuming whole soybean was not the highest observed, the consumption of CP was higher than the other diets, which, associated with a higher DTC, may explain the greater milk production. Naves et al (2016) reported similar values in the milk production of cows consuming whole soybean and a diet without added lipids.…”
Section: Discussionmentioning
confidence: 65%